Approaches, perceptions and conceptions of 3rd year physiotherapy students in a problem-based learning module - Keiller, Lianne (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Centre for Health Sciences Education)--University of Stellenbosch, 2010.